Feasibility Analysis of Rice Field Farming with Hazton Technology Taba System in Meli Village, Donggala Regency - Endah Wahyuning Asih (International Journal of Health, Economics, and Social Sciences (IJHESS), 2021)
The application of technology to increase rice production is carried out in Meli Village, Balaesang District, Donggala Regency by using the Hazton method, namely the technological method in rice cultivation with the number of seeds from 20 to 30 planting holes and the age of the seeds is quite old, around 30-35 days. How much is the production of lowland rice farming with Hazton technology with the Tabela system in Meli Village, Balaesang District, Donggala Regency, and how much is the income and feasibility of lowland rice farming? With Hazton technology with the Tabela system in Meli Village, Balaesang District. Donggala Regency. The average paddy rice production using the Hazton table technology system for respondent farmers in 1 harvest is 6.910 kg/0.8 ha with an average net income of Rp.19,976.348 -/0.8 ha. and an R/C ratio of 4.1. Greater than 1 (Eligible). Assuming each expenditure of Rp. One hundred will earn an income of Rp. 410.